Presence of active myocarditis at the 6 month follow‐up appointment for a severe form of COVID‐19: a case report. (30th July 2021) - Meyer, Maxence; Vogel, Thomas; Meyer, Anita; Constancias, Florentin; Porter, Louise F.; Kaltenbach, Georges; Schmitt, Elise; Chayer, Saïd; Zeyons, Floriane; Riou, Marianne; Fafi‐Kremer, Samira; Velay, Aurélie; et al.
Abstract: Here, we present the case of an 81‐year‐old male patient, who was hospitalized for a severe form of COVID‐19. Transthoracic echocardiogram (TTE) performed 1 month after symptom onset was normal. Respiratory evolution was favourable, and the patient was discharged at Day 78. At 6 months, despite a good functional recovery, he presented pulmonary sequelae, and the TTE revealed a clear reduction of left ventricular ejection fraction (LVEF) and mild LV dilatation without cardiac symptoms. The cardiac magnetic resonance (CMR) using Lake Louise Criteria (LLC), T1 and T2 mapping showed focal infero‐basal LV wall oedema, elevated T1 and T2 myocardial relaxation times especially in basal inferior and infero‐lateral LV walls, and sub‐epicardial late gadolinium enhancement in those LV walls. The diagnosis of active myocarditis was raised especially based on TTE abnormalities and CMR LLC, T1 and T2 mapping. Currently, we are not aware of published reports of a 6 month post‐COVID‐19 active myocarditis.